2010 Re-launch of BJP - McGrath, JC (Blackwell Publishing Ltd, 2010)
BJP has a new look and is re-launching in this first issue of 2010. We have been listening to what authors and readers want from a pharmacology journal and hope that you will choose to submit your best papers here. Similarly, readers will find the best science on how drugs work in every system and at every level. However, the substantial aspects that should attract you are as follows: Impact Factor for 2008 is a highly competitive 4.902. Wider scope – we cover all aspects of pharmacology, molecules to man; translational and integrative bioscience is pharmacology. Free to author colour throughout – print and online. No initial handling charge. No page charges. Open Access policy that meets all funding body requirements. High quality press editing service. PowerPoint downloads of all figures. Downloadable movies and other supporting information files. New Editorial Board and peer-review process. Linked commentaries on exciting or controversial papers. Themed Issues and Sections. Press releases on newsworthy papers. Ensuring the readership for your paper by targeted marketing. This re-launch issue contains a themed section on ‘QT Safety’, dealing with drug-induced toxicities associated with prolongation of the cardiac QT interval (http://www3.interscience.wiley.com/journal/121548564/issueyear?year=2010). Subsequent issues will have themed sections on Imaging in Pharmacology (guest edited by Anthony Davenport and Craig Daly) and GPCRs (guest edited by Roger Summers; following on from the highly successful 2009 GPCR Issue (http://www3.interscience.wiley.com/journal/122575288/issue). Our new, fresh, blue cover design harmonises with our sister journal BJCP's similar green cover, symbolically indicating that our two journals, in the BPS stable, are now working together to cover all of pharmacology. The new design reflects the BPS logo (British Pharmacological Society).